2016
DOI: 10.1136/gutjnl-2016-312135
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of host genetics and gut microbiota underlying the onset and clinical presentation of inflammatory bowel disease

Abstract: ObjectivePatients with IBD display substantial heterogeneity in clinical characteristics. We hypothesise that individual differences in the complex interaction of the host genome and the gut microbiota can explain the onset and the heterogeneous presentation of IBD. Therefore, we performed a case–control analysis of the gut microbiota, the host genome and the clinical phenotypes of IBD.DesignStool samples, peripheral blood and extensive phenotype data were collected from 313 patients with IBD and 582 truly hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

41
511
3
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 651 publications
(564 citation statements)
references
References 49 publications
41
511
3
9
Order By: Relevance
“…Herein, we performed pyrosequencing analysis to investigate whether MIMP can improve the gut dysbiosis in the colitis model. As expected, we observed that DSS treatment caused significantly the decreased diversity of gut microbiota compared with the control group, a finding that is consistent with that in previous studies on IBD patients and the DSS-induced colitis model [34, 35]. In particular, MIMP intervention remarkably increased bacterial diversity and modified the community structure in the colitis mice, as shown by our cluster analysis and PCoA analysis.…”
Section: Discussionsupporting
confidence: 80%
“…Herein, we performed pyrosequencing analysis to investigate whether MIMP can improve the gut dysbiosis in the colitis model. As expected, we observed that DSS treatment caused significantly the decreased diversity of gut microbiota compared with the control group, a finding that is consistent with that in previous studies on IBD patients and the DSS-induced colitis model [34, 35]. In particular, MIMP intervention remarkably increased bacterial diversity and modified the community structure in the colitis mice, as shown by our cluster analysis and PCoA analysis.…”
Section: Discussionsupporting
confidence: 80%
“…First antibiotics may be causally related to IBD, potentially by a mediating effect on the microbiome, causing a reduced diversity and an increased dysbiosis 42. The microbiome interacts with the host through production of short-chain fatty acids (including butyrate), induction of the mucosal immune system, stimulation of the local nervous system and through interaction with the lamina propria by modification of the gut barrier function 43. A dysbiosis in the gut microbiota, characterised by reduction of beneficial bacteria such as Faecalibacterium prausnitzii , and Ruminococcaceae and an increase of pathogens or pathobionts, has consistently been shown in patients with IBD, especially ileal CD 44…”
Section: Discussionmentioning
confidence: 99%
“…We read with interest the recently published work in Gut by Imhann et al 1. Although this paper suggests that genetics plays an important role in IBD,1 environmental factors clearly contribute to its aetiology 2.…”
mentioning
confidence: 96%
“…Although this paper suggests that genetics plays an important role in IBD,1 environmental factors clearly contribute to its aetiology 2. When Ng et al 2 reviewed environmental risk factors for IBD in this journal they noted that urbanisation may be linked to both Crohn’s disease (CD) and ulcerative colitis (UC).…”
mentioning
confidence: 99%